PERANCANGAN PLATFORM INKUBATOR BISNIS SEBAGAI UPAYA PENINGKATAN KOMPETENSI PELAKU UMKM UNTUK MENGGERAKAN PEREKONOMIAN INDONESIA - Pujianto Pujianto; Abdul Rahman; Lindawati Lindawati; Mardiah Kenamon; Rini Efrianti (Universitas Alma Ata, 2022)
AbstractThe role of MSMEs is very large in the Indonesian economy, the contribution of MSMEs is 97% of the workforce and 61.9% of the contribution to the Gross Domestic Product (GDP). However, MSMEs in Indonesia still faces several challenges to developing and improving their business. The Indonesian government implemented stimulus in dealing with and controlling the effects of the Covid-19 pandemic and was effective when compared to other countries. In 2021, Indonesia's real GDP index has reached pre-pandemic conditions at the level of 101.5, while neighboring countries namely Malaysia are at the level of 96.4, the Philippines are at the level of 95.5 and Thailand is still at the level of 94.4. The purpose of this research is to design a Business Incubator Platform in an effort to increase the competency of MSME players through a business incubator. If the competence of MSME players matches current needs, it is hoped that Indonesian MSMEs will be able to compete and improve the Indonesian economy. The method used in this study is the Waterfall Model. While the stages carried out in this method are the stages of system requirements analysis, design, implementation, and system maintenance. While system testing uses the Black Box testing model which focuses on system functionality. The result of this research is an Incubator Platform that can be used by MSME players to improve their business competence. To join this platform, UMKM players register through the platform, after being verified by the admin team, MSME players can use the features that have been provided.